Vegetation Analysis of Tree and Pole Community as Part of Succession in Turgo Hill, Yogyakarta - Santhyami, Santhyami; Aryani, Ima (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
Vegetation analysis is the primary method of ascertaining the structure of the vegetation. This paper aims to analyze the diversity of tree and pole found on Turgo Hill, Sleman Regency, Yogyakarta Special Region following primary succession due to Mount Merapi eruption. Data collection was conducted by sampling plots with a total of 16 sampling plots consisting of 8 plots of 20x20m for trees and 8 plots of 10x10m for poles. A total of 91 individuals composed of 60 trees and 31 poles, were observed in the sampling area. Based on Importance Value (IV), the most dominant tree species is Swietenia mahagoni (IV 116,38%), followed by Artocarpus Heteropyllus (IV 32,7%), and Meiopsis eminii (IV 24,12%). The most dominant pole species is Swietenia mahagoni (IV 60,78%) followed by Durio zibenthius (IV 37.16%) and Albizia chinensis (IV 36.38%). It can be concluded that Swietenia mahagoni is the most dominated tree and pole species.